2001
DOI: 10.1021/jf001177f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Sodium Chloride in Cured Salmon Roe by SW−NIR Spectroscopy

Abstract: Salt and moisture content of cured salmon roe (ikura) was determined using short-wavelength-near-infrared (SW-NIR) reflectance spectroscopy (600-1100 nm). SW-NIR can be used to measure chloride species. Calibrations for salt in bulk samples of high-quality roe (R(2) = 0.904, SEP = 0.421%, RPD = 3.21) and average-quality roe (R(2) = 0.711, SEP = 1.13%, RPD = 1.81), crushed eggs (R(2) = 0.857, SEP = 0.509%, RPD = 2.62), and individual eggs (R(2) = 0.731, SEP = 0.698%, RPD = 1.98) were developed using partial lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 16 publications
1
53
0
3
Order By: Relevance
“…Other optical methods have been studied for food quality lately by many researchers, for example, Farkas and Dalmadi [5], Kaffka [6], and Huang et al [7]. The optical methods could alleviate these problems although they are not so accurate.…”
Section: Historymentioning
confidence: 99%
See 2 more Smart Citations
“…Other optical methods have been studied for food quality lately by many researchers, for example, Farkas and Dalmadi [5], Kaffka [6], and Huang et al [7]. The optical methods could alleviate these problems although they are not so accurate.…”
Section: Historymentioning
confidence: 99%
“…Another advantage of optics is that it can be imaging and thus characterizing the sample better. A popular spectral area for food research has been near-infrared (NIR) in which many publications can be found like Huang et al [7], Pallav et al [8], Ozaki et al [9], and Osborne [4].…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the large number of publications dealing with hyperspectral imaging spectroscopy and its promising results [12], [13] in the field of food quality, this seems to be a good way to attain a reliable low cost system to measure the freshness of fish, addressing industrial requirements [14]. Furthermore, spectroscopy in the range of visible and short wave infrared (SW-NIR) is specially indicated to evaluate chemical composition and quality in fish [15][16][17][18]. New works apply hyperspectral imaging spectroscopy in the SW-NIR range [19], [20] for evaluating freshness in fish.…”
Section: Introductionmentioning
confidence: 99%
“…Determination of salt concentration in food products is critical to ensure food safety and quality [2]. SW-NIR can be used to predict salt content in cured and/or smoked fish roe and fillets, and potentially to monitor changes in the salt concentration of brines that provides a means for predicting salt absorption rate in food samples during processing [2][3][4].…”
Section: Introductionmentioning
confidence: 99%